TEKNIK BERTUTUR DALAM MENYAMPAIKAN PESAN PADA LATIHAN KIHON KARATE DI DOJO RAUDHATUL JANNAH - Mhd. Johan; Winda Evyanto; Gaguk Rudianto; Robby Satria; Zia Hisni Mubarak; Yunisa Oktavia (ASOSIASI IDEBAHASA KEPRI, 2023)
Kihon or basic movements are what every karate-ka must learn in practice. This basic movement is a movement where a karateka can start other movements. The purpose of this research is to improve the performance of junior athletes. If the basic movements cannot be carried out properly and correctly, it will have an impact on other movements. If the message to be conveyed is not clear, the students cannot carry out the movement properly. Therefore, a coach must have knowledge in conveying language to his students. The method used in this exercise is the trainer demonstrating basic movements in accordance with basic of the karate standards. Therefore, the coach must be able to communicate with kohai properly and correctly. In addition to linguistics, the trainer must also provide examples of good movement as well. In this exercise the trainer still finds movements that are not adequate in practice, so they need to be corrected and practiced regularly.